Heterotopic gastric mucosa of the umbilicus: A rare cause of umbilical nodule - Thara Keloth; V. Sriram; Ramya Gandhi; Erli Amel Ivan (Journal of Current Research in Scientific Medicine)
Umbilical discharge is a commonly encountered problem in infants, with common causes being omphalitis and umbilical granuloma. Unusual causes of persistent umbilical discharge are remnants of the omphalomesenteric duct and the urachus. Heterotopic or ectopic tissues at the umbilicus are rare events that cause umbilical discharge and these mandate a surgical intervention. Gastric heterotopia at the umbilical region is such an unusual entity causing persistent discharge and chemical dermatitis around the region, which needs surgical intervention. We hereby report a rare case of gastric heterotopia of the umbilicus in an 8-month-old male baby.